DESCARTES’ MATHEMATICAL IDEAS IN THE EARLIEST LITHUANIAN TEXTBOOKS - Algirdas Ažubalis (Problemos)
In mathematics R. Descartes was the first to arrange algebraical symbolics and to ground the method of equations, analytic goemetry, the coordinate system, and the concept of function. He was also the firs to approach the methods of differential and integral calculations. The first Lithuanian book of problems in arithmetic was issued in 1885 (prepared by J. Spudulis and P. Matulionis), the P. Vileišis textbook of arithmetic theory being issued in 1886. Both books are based on the method of equations. Algebraical symbolics was first presented in Lithuanian by A. Smetona in a translated textbook. The introduction of the concept of function into mathematics courses in school was initiated by Professor Z. Žemaitis’, whose idea was realized in algebra textbooks by J. Mašiotas, Z. Balutis-Balevičius, M. Šikšnys, J. Dailidė, and by A. Dambrauskas-Jakštas in trigonometry textbooks. Textbooks of higher mathematics for schools were written by J. Stoukus, B. Ketarauskas, A. Juška and J. Gailevičius, while those for universities were prepared by O. Folkas, P. Katilius, Z. Žemaitis and Vikt. Biržiška.